2022
DOI: 10.1080/21645515.2021.2018863
|View full text |Cite
|
Sign up to set email alerts
|

Usability, acceptability, and feasibility of a High-Density Microarray Patch (HD-MAP) applicator as a delivery method for vaccination in clinical settings

Abstract: Background High-density microarray patch (HD-MAP) vaccines may increase vaccine acceptance and use. We aimed to ascertain whether professional immunizers (PIs) and other healthcare workers (HCWs) in Australia, a High-Income Country (HIC), found the HD-MAP applicator usable and acceptable for vaccine delivery. Methods This feasibility study recruited PIs and HCWs to administer/receive simulated HD-MAP administration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Confidence in correct administration was relatively low, with only half of the participants in two clinical studies confident that the MAP would have worked in general 38 43. However, in another study, all participant groups were confident that they correctly self-administered a MAP 45. Two studies suggested a visual indicator to confirm a correct MAP dose delivery as an improvement to MAP design, which was reported by all laypeople and most HCPs 48 49.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Confidence in correct administration was relatively low, with only half of the participants in two clinical studies confident that the MAP would have worked in general 38 43. However, in another study, all participant groups were confident that they correctly self-administered a MAP 45. Two studies suggested a visual indicator to confirm a correct MAP dose delivery as an improvement to MAP design, which was reported by all laypeople and most HCPs 48 49.…”
Section: Resultsmentioning
confidence: 98%
“…Quantitative and qualitative data explored usability and acceptability. Across several studies, HCPs, HCWs and laypeople found MAPs very easy to use 15 44 45. One clinical study in the USA compared MAPs with and without a snap-based device, each administered three times 8.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several usability studies have been published indicating the general ease of use of Vaxxas MAP technology in both low/middle income and high-income countries, but both studies also highlighted the need for significant user education around technology introduction. 22 , 23 …”
Section: Challenges In Making the Shift To Vaccine Maps A Commercial ...mentioning
confidence: 99%
“…We have experience with a high-density microarray patch (HD-MAP) vaccine delivery platform. The HD-MAP applied to the skin provides practical advantages, including the absence of sharps, a reduced dependence or total removal from the cold chain, and the possibility for self-application through the use of a disposable applicator [5][6][7]. The HD-MAP delivers the vaccine antigen to the epidermal and dermal layers of the skin containing a high density of dendritic cells.…”
Section: Introductionmentioning
confidence: 99%